Drivers and epidemiological patterns of West Nile virus in Serbia - Marini, Giovanni; Drakulovic, Mitra B.; Jovanovic, Verica; Dagostin, Francesca; Wint, Willy; Tagliapietra, Valentina; Vasic, Milena; Rizzoli, Annapaola (Frontiers in Public Health, 2024)
West Nile virus (WNV) is an emerging mosquito-borne pathogen in Serbia, where it has been detected as a cause of infection in humans since 2012. We analyzed and modeled WNV transmission patterns in the country between 2012 and 2023.We applied a previously developed modeling approach to quantify epidemiological parameters of interest and to identify the most important environmental drivers of the force of infection (FOI) by means of statistical analysis in the human population in the country.During the study period, 1,387 human cases were recorded, with substantial heterogeneity across years. We found that spring temperature is of paramount importance for WNV transmission, as FOI magnitude and peak timing are positively associated with it. Furthermore, FOI is also estimated to be greater in regions with a larger fraction of elderly people, who are at higher risk to develop severe infections.Our results highlight that temperature plays a key role in shaping WNV outbreak magnitude in Serbia, confirming the association between spring climatic conditions and WNV human transmission risk and thus pointing out the importance of this factor as a potential early warning predictor for timely application of preventive and control measures.